Using oral activities to teach grammar communicatively to first year non English major students at Vietnam University of Commerce - Trần, Thị Thu Hiền (University of Languages and International Studies, 2017)
Chapter one, Literature Review, provides the theoretical background for the thesis. This chapter includes three main points. The first point deals with the general view on grammar and grammar teaching approaches. The second point discusses the problems. Finally, the third point discusses the need for applying oral activities to grammar teaching. Chapter two, The Study, aims to describe background information about the current teaching and learning of grammar at VCU and presents the methodology underlying the research including data collection instruments, procedures. A detailed data analysis and discussions are also given .